ENGAGE EVENT MANAGEMENT APPLICATION (EEMA) - Balakrishnan, Ragulan (IRC, 2019)
Information technology (IT) has changed how organizations run their businesses. Many organizations now use IT tools to solve complex problems and plan for future growth of their business or firm. The event management industry is no exception, IT has dominated the industry at a huge scale and has changed the industry forever, not only changing but it is developing into an interactive industry. Event management is the planning and management of an event, project or activity and event is something that happens, it would not just exist without somebody who have to make it happen. Successful events only come about through action, some individual or group of individuals getting things done. IT has been used not only in promoting, but also in service providing. In order to attract loyal and satisfied customers, event planners in particular must reach to customers and understand them better. A system could cater to this by providing event planners and customers a platform for information and communication. However, there are no actual mobile based application that are being used currently in Malaysia. The aim of this project is to develop an application that acts as a platform for information and communication between two parties called Easy Event Management Application (EEMA). The objective is to make possible for customers to make an appointment with event planners, view their service, history, keep track on the services performed, while organizers are able to view the appointments made, keep a history record of the organizers that have received their services and many more. Many researchers have been conducted on the natures and general requirements of customers through the internet, and event planners were also being interviewed in order to gather their requirements. Diagrams such as user diagram, system architecture. Web navigation and a prototype graphical user interface were also developed in the process. A working prototype of EEMA will be developed to cater all the requirements needed by customers generally.